Polymer Microfluidics Chip Fabrication and Its Energy Application: A Mini Review - Sandi, Dianisa; Li, Yang; Evan, Bah; Efendi, Erwan Tri; Huda, Luqman Al; Fajri, Amrisal Kamal; Prihatmini, Eri (Eksergi, 2025)
Microfluidics is a technology that manipulates fluids at a microscale and has shown great potential in various fields, including energy. This mini-review discusses common microfluidic materials and the main techniques in microfluidic chip fabrication, such as photolithography, soft lithography, and 3D printing-based fabrication methods. Furthermore, several applications of microfluidic chips in the energy sector, such as solar energy and fuel cell systems development, are also discussed. The use of microfluidic chips in energy systems offers high efficiency, low material consumption, and good system integration. This review aims to provide an overview of the progress of microfluidic chip fabrication and its energy potential applications.